Sharing reserves through HVDC: Potential cost savings in the Nordic countries. Issue 3 (8th December 2020) - Tosatto, Andrea; Dijokas, Matas; Weckesser, Tilman; Chatzivasileiadis, Spyros; Eriksson, Robert
Abstract: During summer 2018, the Nordic system's kinetic energy dropped below a critical level. As a consequence, Svenska kraftnät, the Swedish transmission system operator, requested the largest production unit to reduce its power output to guarantee system's security. This action resulted in a deviation from the generation dispatch determined by the market and in high costs for the Nordic transmission system operators. In this regard, this paper presents a tool for comparing mitigation strategies from an economic point of view and evaluates potential economic benefits of utilizing the emergency power control functionality of high‐voltage direct current lines for the provision of fast reserves as a compliment to frequency containment reserves. Moreover, the analysis is extended to the years 2020 and 2025 using inertia estimations from the Nordic transmission system operators. The findings of the paper suggest that the frequency of redispatching actions will increase in the future and that the cost of security for Nordic transmission system operators could be reduced by 70% if high‐voltage direct current links are used for frequency support.